2016
DOI: 10.1111/and.12682
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofLepidium meyenii(maca) on testicular function of mice with chemically and physically induced subfertility

Abstract: The aim of this study was to evaluate the effect of Lepidium meyenii (maca) in chemically and physically subfertile mice. After 35 days, the following groups of mice were evaluated: control, sham, chemical subfertility, chemical subfertility-maca-supplemented, physical subfertility, physical subfertility-maca-supplemented and maca-supplemented only. Motility (32.36% ± 5.34%) and sperm count (44.4 ± 5.37 × 10(6) /ml) in the chemically and physically subfertile mice (11.81% ± 4.06%, 17.34 ± 13.07 × 10(6) /ml) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In total, 75 studies focused on plant derived compounds, five studies on animal derived compounds, and only one study presented a natural substance of fungal origin. Natural products which were mentioned more than once include Curcumin, Echinacoside, and extracts from Cistanche tubulosa , Date palm pollen, Diallyl sulfide , Lycium barbarum , Linn., Lepidium meyenii Walp., Morinda oleifera Lam, and Tribulus terrestis Linn [ 6 , 9 , 22 , 50 , 51 , 54 , 55 , 63 , 64 , 65 , 104 , 105 ]. Especially, the effects of Tribulus terrestis Linn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 75 studies focused on plant derived compounds, five studies on animal derived compounds, and only one study presented a natural substance of fungal origin. Natural products which were mentioned more than once include Curcumin, Echinacoside, and extracts from Cistanche tubulosa , Date palm pollen, Diallyl sulfide , Lycium barbarum , Linn., Lepidium meyenii Walp., Morinda oleifera Lam, and Tribulus terrestis Linn [ 6 , 9 , 22 , 50 , 51 , 54 , 55 , 63 , 64 , 65 , 104 , 105 ]. Especially, the effects of Tribulus terrestis Linn.…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully demonstrate the efficacy of the natural products, it is necessary to progress a properly designed experiment that is targeted on models that induced reproductive toxicity in advance. Moreover, several studies were progressed with high doses, especially maca capsule and extract were treated using more than 500 mg/kg [ 64 , 65 ]. Two of three studies that reported the efficacy of Moringa oleifera used more than 100 mg/kg [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous maca extract at a dose of 2.2 g/Kg daily in rats was also found to reverse the damaging effect of lead acetate on Stages VII, VIII and IX–XI on seminiferous epithelium length and maintained corpus and cauda epididymis sperm count, daily sperm count and spermatid count (Rubio et al, 2006 ). A study by Valdivia Cuya et al ( 2016 ) of maca on chemically and physically induced sub‐fertility in mice also gave concurring results with 666 mg/Kg BW daily of aqueous extract. Maca was also reported to have potential use in treating erectile dysfunction related to hypogonadism and microvascular damage in diabetes (Kimura et al, 2016 ; Zheng et al, 2000 ).…”
Section: Discussionmentioning
confidence: 60%
“…Due to this, a nutritional supplement proven in fertility ( Lipidium meyenii “maca”) was proposed to counteract physically‐induced infertility by MFs. Although a decrease in DNA fragmentation was obtained, no recovery was observed in sperm motility [Valdivia et al, ] which is produced when mitochondrial activity has been affected. That is why this study's objective was to search for a powerful agent that can reverse damage to the mitochondrial sperm membrane due to free radicals from ELF‐MF exposure, in order to determine a possible application in human beings, contributing to public health.…”
Section: Introductionmentioning
confidence: 99%